Impacts of intensive care patients' oral hygiene on nosocomial and ventilator-associated pneumonia: integrative literature review (Research, Society and Development, 2021)
Hospital Dentistry has been gaining field, since several successful experiences, associated with scientific evidence have shown that dental care at the hospital level can contribute to the reduction of cases of nosocomial pneumonia associated with mechanical ventilation, thus reducing the length of hospital stay and consequently the costs of this process. The objective of this study was to verify the efficacy of oral hygiene protocols in ICU patients in the prevention of ventilator-associated pneumonia or nosocomial pneumonia. An integrative literature review was carried out with searches in the Pubmed/MEDLINE and Scielo databases, in which 23 articles were selected for qualitative analysis after application of the eligibility criteria guided by the PRISMA strategy. We noticed that the use of chlorhexidine seems to be the most recurrent protocol in the studies, with better results when associated with the mechanical adequacy provided by brushing, in reducing the cases of nosocomial pneumonia. Other methods such as the use of povidone-iodine and supraglottic aspiration were mentioned, although their effects are still controversial. Thus, we conclude that although there is not a well-defined protocol for the control of oral biofilm and consequent reduction in the prevalence of pneumonia, chlorhexidine associated with brushing seems to be the most promising method. More studies with robust methodology are needed for the understanding and proposal of protocols based on scientific evidence for oral hygiene of patients in intensive care, focused on reducing morbidity and mortality from nosocomial pneumonia.